IMPLEMENTASI PERBUB BUPATI NOMOR 13 TAHUN 2023 TENTANG PENATAAN DAN PEMBERDAYAAN PEDAGANG KAKI LIMA DI KECAMATAN SITUBONDO KABUPATEN SITUBONDO - Giyanto, Giyanto -; Hanum, Farida; Senain, Senain; Aini, Dini Noor; latifa, Sofia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Abdurachman Saleh Situbondo, 2025)
The existence of more and more street vendors often has a negative impact, especially on environmental issues. Where the environment becomes slum and also disturbs public facilities and motorists; besides that, it also disturbs the order, beauty, and neatness of the Situbondo Regency roads. Based on this, the Situbondo Regency Government formulated a policy in Regent Regulation Number 13 of 2023 concerning the Arrangement and Empowerment of Street Vendors. This study aimed to determine the implementation of Regent Regulation Number 13 of 2023 concerning the Arrangement and Empowerment of Street Vendors in Situbondo District at the Office of Cooperative, Industry, and Trade in Situbondo Regency. This research uses descriptive qualitative methods. This research is located on W.R. Supratman Street and Anggrek Street, Situbondo Regency, and at the Office of Cooperative, Industry, and Trade. The data collection methods in this study are interviews, observation, and documentation. Based on the results of the study, it can be concluded that the Implementation of Regent Regulation Number 13 of 2023 concerning the Arrangement and Empowerment of Street Vendors in Situbondo District at the Office of Cooperative, Industry, and Trade in Situbondo Regency is reviewed by the George C. Edward III theoretical model. Edward III's theoretical model needs to be maximally implemented. This is because the four dimensions of Edward's theory still need to be implemented, which consist of communication, resources, disposition, and bureaucratic structure.